(untitled) (Journal of Philosophy Culture and Political Science, 2024)
Contemporary post/decolonial discourses in Kazakhstan have completely excluded the following issues from the field of narrative. First, the issue of ‘colonial complicity’, that is the fact that colonization was carried out with the direct participation of the local population. Second, is the issue of re-evaluation of the pre-colonial political and social structure. In other words, Kazakh society tries to forget that even before colonialism the society already was in a deep crisis. Kazakh society is unwilling to critically reassess the pre-colonial period. Thus, this research aims to critically assess the post/decolonial discourses that consider current political and social issues mostly as a result of colonialism and overemphasize external factors. Keywords: postcolonial Kazakhstan, colonial complicity, modernity/coloniality, pre-colonial political and social structure, discourse analysis, rewriting history